Possible origin of Triticum petropavlovskyi based on cytological analyses of crosses between T. petropavlovskyi and tetraploid, hexaploid, and synthetic hexaploid (SHW-DPW) wheat accessions - Chen, Qian; Song, Jun; Du, Wen-Ping; Xu, Li-Yuan; Yu, Gui-Rong (Spanish Journal of Agricultural Research, 2016)
Intraspecific hybridization between Triticum petropavlovskyi Udacz. et Migusch., synthetic hexaploid wheat (SHW-DPW), and tetraploid and hexaploid wheat, was performed to collect data on seed set, fertility of F1 hybrid, and meiotic pairing configuration, aiming to evaluate the possible origin of T. petropavlovskyi. Our data showed that (1) seed set of crosses T. petropavlovskyi × T. polonicum and T. petropavlovskyi × T. aestivum cv. Chinese Spring was significantly high; (2) fertility of hybrids T. petropavlovskyi × T. polonicum and T. petropavlovskyi × T. aestivum ssp. yunnanense was higher than that of the other hybrids; (3) fertility of F1 hybrids SHW-DPW × T. dicoccoides and SHW-DPW×T. aestivum ssp. tibetanum was significantly high; and (4) c-value of T. petropavlovskyi × T. polonicum and T. petropavlovskyi × T. aestivum cv. Changning white wheat was also significantly high. The results indicate that the probable origin of T. petropavlovskyi is divergence from a natural cross between T. aestivum and T. polonicum, via either spontaneous introgression or breeding effort.